The Legal Framework for Protecting Social Security Rights of the Elderly in Tanzania - Temba, Ferdinand (Journal of Policy and Leadership, 2025)
The right to social security is crucial for ensuring social justice, particularly for the elderly who are at heightened risk of poverty. This study examines the legal framework for social security in Tanzania, using doctrinal research to analyse relevant national laws and policies. It begins by outlining the importance of social security and assessing global and regional instruments that protect these rights. The findings reveal that while the Constitution outlines fundamental rights, it does not establish an enforceable right to social security for the elderly. The study highlights the challenges facing universal pension programs, such as the Tanzania Social Action Fund (TASAF) and the Productive Social Safety Net (PSSN). Key issues include enforcement difficulties, insufficient resource allocation, and social exclusion. To address these challenges, the study recommends the development of a comprehensive legal framework that reinforces compliance with international norms and enhances administrative capabilities. Furthermore, it suggests legal reforms aimed at expanding coverage and improving access to social security for the elderly, emphasising the need to tackle issues of inequality and poverty. The analysis incorporates international instruments, such as the ILO Social Security (Minimum Standards) Convention and the SADC Social Charter, to examine Tanzania's adherence to these standards. By advocating for policy improvements and legal reforms, the study contributes valuable insights into strengthening social security rights for the elderly in Tanzania, thereby promoting social inclusion and reducing poverty.